EU foreign policy through the lens of discourse analysis making sense of diversity (Globalisation, Europe, multilateralism, 2016)
Leading scholars in discourse analysis and European foreign policy join forces in this book, marking a real breakthrough in the literature. Not only do they offer original perspectives on European foreign policy, but they bring together various theories on foreign policy discourses that remain too often isolated from each other.